Analisis Isi dalam Penelitian Pembelajaran Bahasa dan Sastra - Sumarno Sumarno (Edukasi Lingua Sastra, 2020)
Content analysis can be widely applied in language and literature learning in schools, for example to: describe learning trends (trends); know learning patterns / models; uniqueness of the school / teacher in overcoming problems; predict attitudes, values and school cultural patterns; describe teacher perceptions; and describe learning management ideas. In addition, it can also be used for language and literary research, such as critical discourse analysis, describing elements of literary works, values of literary works, and readers' perceptions of literary works. Content analysis requires researchers who have and can take advantage of their analytical acumen to knit the content of communication phenomena into socially readable phenomena.